Defining intercultural education for social cohesion in Malaysian context - Kaur, Amrita; Awang Hashim, Rosna; Noman, Mohammad (Eastern University, 2017)
Schools are considered as powerful institutions that are capable of fostering a sense of coherence and common identity to integrate students of different ethnic, social, and cultural origins. Effective implementation of intercultural education at schools can facilitate social integration. However, it is important that the design and implementation of intercultural education be guided by the knowledge and understanding of the issues and patterns of discrimination and complexities within its context. This qualitative study explored perspectives of key stakeholders involved in the education process to define a framework for intercultural education in Malaysian context for successful social cohesion. The findings are discussed in terms of practical application for educators, researchers, and policymakers.